Influence of barium (Ba2+) doping for Cu-Zn ferrites on structural and electrical properties. (2020) - Tandon, Vishal; Saleem, M.; Kaurav, Netram; Dixit, R.C.
Abstract: This report throws light on the synthesis and characterization of the Cu-Zn ferrites of the type Cu0.5-x Ba x Zn0.5 Fe2 O4 [ x  = 0, 0.05, 0.1]. The solid state reactions route was used for synthesis of ferrites under consideration. To confirm the structure, phase and lattice formation, these materials were characterized by X-Ray diffraction and Raman spectroscopic techniques. In addition to the structural study, the samples were investigated for dielectric. The XRD data analysis conferred that all the prepared samples have acquired cubic structure and exhibit Fd 3 m space group. The diffractograms are same in appearance with no new reflection visible in the limits of experimentation revealing the sample to be mono-phase in nature. With the display of signature vibration modes by all the samples, the lattice structure formation was confirmed. The dielectric studies showed the ferrites under study to be exhibiting low dielectric constant with low decreasing rate with increase in the applied field. Furthermore, the samples have low loss values which increase their ability for advanced technological applications.